Blue ocean strategy how to create uncontested market space and make the competition irrelevant - Kim, W. Chan; Mauborgne, Renée (Harvard Business Review Press, 2015)
Blue ocean strategy presents a systematic approach to making the competition irrelevant and outlines principles and tools any organization can use to create and capture their own blue oceans. This expanded edition includes: A new preface by the authors: Help! My Ocean Is Turning Red Updates on all cases and examples in the book, bringing their stories up to the present time Two new chapters and an expanded third one--Alignment, Renewal, and Red Ocean Traps --that address the most pressing questions readers have asked over the past 10 years A landmark work that upends traditional thinking about strategy, this bestselling book charts a bold new path to winning the future. Consider this your guide to creating uncontested market space--and making the competition irrelevant.